1923 Conn. Pub. Acts 3708 - (:unkn) unknown (My University, 1923)
An Act Concerning the Possession, Sale and Use of Pistols and Revolvers, ch. 252, § 5: Prohibited the sale of any pistol or revolver in any location not described in the permit allowing such sales. Prohibited the sale or delivery of any pistol or revolver unless the purchase or recipient of such pistol or revolver is personally known to the vendor.
Keywords: TRANSFER